Debaryomyces Hansenii Supplementation in Low Fish Meal Diets Promotes Growth, Modulates Microbiota and Enhances Intestinal Condition in Juvenile Marine Fish - Reyes-Lopez, F (BioMed Central Ltd, 2023)
Background: The development of a sustainable business model with social acceptance, makes necessary to develop new strategies to guarantee the growth, health, and well-being of farmed animals. Debaryomyces hansenii is a yeast species that can be used as a probiotic in aquaculture due to its capacity to i) promote cell proliferation and differentiation, ii) have immunostimulatory effects, iii) modulate gut microbiota, and/or iv) enhance the digestive function. To provide inside into the effects of D. hansenii on juveniles of gilthead seabream (Sparus aurata) condition, we integrated the evaluation of the main key performance indicators coupled with the integrative analysis of the intestine condition, through histological and microbiota state, and its transcriptomic profiling. Results: After 70 days of a nutritional trial in which a diet with low levels of fishmeal (7%) was supplemented with 1.1% of D. hansenii (17.2 × 105 CFU), an increase of ca. 12% in somatic growth was observed together with an improvement in feed conversion in fish fed a yeast-supplemented diet. In terms of intestinal condition, this probiotic modulated gut microbiota without affecting the intestine cell organization, whereas an increase in the staining intensity of mucins rich in carboxylated and weakly sulphated glycoconjugates coupled with changes in the affinity for certain lectins were noted in goblet cells. Changes in microbiota were characterized by the reduction in abundance of several groups of Proteobacteria, especially those characterized as opportunistic groups. The microarrays-based transcriptomic analysis found 232 differential expressed genes in the anterior-mid intestine of S. aurata, that were mostly related to metabolic, antioxidant, immune, and symbiotic processes. Conclusions: Dietary administration of D. hansenii enhanced somatic growth and improved feed efficiency parameters, results that were coupled to an improvement of intestinal condition as histochemical and transcriptomic tools indicated. This probiotic yeast stimulated host-microbiota interactions without altering the intestinal cell organization nor generating dysbiosis, which demonstrated its safety as a feed additive. At the transcriptomic level, D. hansenii promoted metabolic pathways, mainly protein-related, sphingolipid, and thymidylate pathways, in addition to enhance antioxidant-related intestinal mechanisms, and to regulate sentinel immune processes, potentiating the defensive capacity meanwhile maintaining the homeostatic status of the intestine. © 2023, The Author(s).